Determinants of Remittances : Recent Evidence Using Data on Internal Migrants in Vietnam - Niimi, Yoko; Pham, Thai Hung; Reilly, Barry (World Bank, Washington, DC, 2012)
This paper examines the determinants of remittance behavior for Vietnam using data from the 2004 Vietnam Migration Survey on internal migrants. It considers how, among other things, the vulnerability of a migrant's life at the destination, their link to relatives back home, and the time spent at the destination affect remittances. The paper finds that migrants act as risk-averse economic agents and send remittances back to the household of origin as part of an insurance exercise in the face of economic uncertainty. Remittances are also found to be driven by a migrant's labor market earnings level. The paper highlights the important role of remittances in providing an effective means of risk-coping and mutual support within the family.